Integrative Learning Models For Numeracy Literacy And Character Development: Insights From A Bibliometric Analysis - Yulindaria, Lia; Yadi; Encep; Asep (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This research aims to map global trends in integrative learning models that combine numeracy literacy and character development, to provide in-depth insight into the contributions of existing research and the gaps that need to be addressed. Method: The method used is quantitative-based bibliometric analysis, with data collected from the Scopus database in the time period 2002–2024. Analysis was carried out using VOSviewer and R-Studio software to identify publication patterns, collaboration networks between authors and institutions, and dominant research themes. Results: The research results show a significant increase in related publications since 2016, with a peak in research activity in 2024. The main findings indicate that the topics of numeracy literacy and character development are increasingly gaining global attention, with the largest contributions coming from the fields of social sciences, computer science, and education. Co-occurrence analysis reveals that terms such as